Antidiabetic And Antihyperlipidemic Effect Of Morin On Lipids And Lipoproteins In Streptozotocin-Induced Diabetic Rats - S.VISHNUKUMAR,; R.STEPHAN,; S.CHANDRA, (International Journal of Pharma and Bio Sciences, 2012)
The potential role of morin in the treatment of diabetes along with its antihyperlipedemic effects was studied in streptozotocin-induced diabetic rats. Diabetes was induced in male Wister rats by single intraperitoneal injection (i.p) of 50 mg/kg streptozotocin. Morin was administered orally at doses of 50 and 100 mg/kg for 45 days. At the end of this experiment the effect of morin on plasma glucose, insulin, and serum triglycerides, phospholipids, free fatty acids, total cholesterol, very low density lipoprotein, low density lipoprotein and high density lipoprotein were studied. Administration of morin to diabetic rats resulted in a significant reduction in the elevated levels of plasma glucose, as well as lipids and very low density lipoprotein and low density lipoprotein levels. The decreased plasma insulin and serum high density lipoprotein in diabetic rats were also reversed towards near normal. The results indicates that the administration of morin to diabetic rats normalized plasma glucose, insulin concentrations and caused marked improvement in altered lipids, lipoproteins. Our results show the antihyperlipedemic properties of morin in addition to its antidiabetic action. Moreover, the antihyperlipedemic effect could represent a protective mechanism against the development of atherosclerosis.